Efficient Differentiation of Cardiomyocytes from Human Pluripotent Stem Cells with Growth Factors - Jha, Rajneesh (Methods Mol Biol, 2015)
Human pluripotent stem cells have tremendous replicative capacity and demonstrated potential to generate functional cardiomyocytes. These cardiomyocytes represent a promising source for cell replacement therapy to treat heart disease and may serve as a useful tool for drug discovery and disease modeling. Efficient cardiomyocyte differentiation, a prerequisite for the application of stem cell-derived cardiomyocytes, can be achieved with a growth factor-guided method. Undifferentiated cells are sequentially treated with activin A and BMP4 in a serum-free and insulin-free medium and then maintained in a serum-free medium with insulin. This method yields as much as >75% cardiomyocytes in the differentiation culture within 2 weeks, and the beating cardiomyocytes have expected molecular, cellular and electrophysiological characteristics. In this chapter, we describe in detail the differentiation protocol and follow-up characterization focusing on immunocytochemistry, quantitative RT-PCR and flow cytometry analysis.